The 'plant economic spectrum' in bryophytes, a comparative study in subalpine forest. Issue 2 (17th February 2017) - Wang, Zhe; Liu, Xin; Bader, Maaike Y.; Feng, Defeng; Bao, Weikai
Abstract : PREMISE OF THE STUDY: Tradeoffs among functional traits of vascular plants are starting to be better understood, but it is unclear whether bryophytes possess similar tradeoffs or how trait relationships, or the 'economic spectrum', differ between the two groups. METHODS: We determined functional‐trait values [including shoot mass per area (SMA), light‐saturated assimilation rate (Amass ), dark respiration rate (Rdmass ), N and P concentrations (Nmass and Pmass ), and photosynthetic N and P use efficiency (PNUE and PPUE)] and their bivariate relationships for 28 bryophytes growing in a subalpine old‐growth fir forest on the eastern Tibetan Plateau. Trait values and scaling relationships of these bryophytes were compared with data for vascular plant leaves from the Global Plant Trait Network (GLOPNET) dataset. KEY RESULTS: We found that the Amass, Nmass, N:P, PNUE and PPUE of bryophyte shoots were lower than those of vascular plant leaves. In contrast, bryophytes possessed higher Pmass and the two groups had similar values of SMA and Rdmass . The Nmass and Pmass were closely associated with Amass and Rdmass, and these traits were all significantly negatively related to SMA. Metabolic rates increased faster with nutrient concentrations in bryophytes than in vascular plants. CONCLUSIONS: Our research indicates that bryophytes have similar trait relationships as vascular plant leaves, although the slopes of the relationships differ for most trait combinations. This study confirms a functional‐trait tradeoff in bryophytes, and reveals that bryophytes allocate greater proportions of N and P into the metabolic pools.